Leaf microstructure and adaptation relationships in ten woody species from the semi-arid forests - Soheili, Forough; Panahi, Parisa; Hatamnia, Ali Asghar; Woodward, Stephen; Abdul-Hamid, Hazandy; Naji, Hamid Reza (Iranian Society of Forestry, 2023)
Micro-morphological characteristics of leaves such as stomata and trichomes are reliable indicators of plant response to environmental conditions. The aim of this study was to determine the adaptation strategies of 10 woody species growing in semi-arid Zagros forests in western Iran based on leaf microstructures, focusing on trichomes and stomata using light and scanning electron microscopy. Different types of trichomes and stomata were recognized. Stomata were generally more visible on the abaxial sides of leaves, a feature that helps reduce water loss from leaf surfaces exposed to direct airflow and radiation. Trichomes were classified into two different types: glandular trichomes and non-glandular trichomes with subgroups such as solitary, two-armed T-shaped unicellular, crypt, hooked hairs with cystoliths, fasciculate, stellate, long coiled, tufted stellate, long multiradiate, short bristles with cystoliths, peltate scales, and dendritic hairs. The abundance of trichomes on the leaves indicates their role as biological control parameters. Eucalyptus camaldulensis was the only introduced species studied that lacked trichomes on both sides of the leaf. The most frequently observed types of stomata were "Anomocytic" and "Paracytic". The striking differences between the micro-morphological characteristics of the leaves of different species are an expression of the plants adaptations to the environmental ecological conditions.